Health workers’ perception of user violence in the Talcahuano Health Service in Lirquén, Chile, 2017 - Vega-Pinochet, Hugo (Revista Chilena de Salud Pública, 2019)
Introduction: Violence in health centers, which historically affected only a few occupations, is now widespread. The prevalent exposure of workers to aggressions has a negative impact on their safety and health. Objective: To describe user violence perceived by health workers of the Talcahuano Health Service in Lirquén, Chile. Methods. A cross-sectional descriptive study was conducted, with 155 participants who were workers in two health centers, belonging to the Talcahuano Health Service, in 2017. After going through an informed consent process, participants answered a validated, self-applied, anonymous, and confidential instrument. Analysis is presented with distribution tables, averages, and dispersion data. Results: It was found that 70.3% of workers reported having suffered violence by users, and that 85.3% of that violence was verbal. The most affected workers were doctors, dentists, and nurses. The acts of violence occurred tended to occur in the morning, while users waited to be seen or during their appointment; the main causes were wait time and the users’ mental health. The aggressors were adult users, of both sexes. Finally, only 9.2% of the attacks were formally reported; 30% of the workers believe that registering the violence is useless; and 72.5% consider that the amount of violence remains the same or is increasing. Conclusions: User violence affects the majority of health workers. There is minimal formal notification and scarce registration of the aggressions. Workers should be trained to prevent and address these aggressions.